9 x 9 -- A Method of Design : From City to House Continued. - Eberle, Dietmar, 1952- (De Gruyter : Birkhäuser, 2018)
An ideal design is site-specific, which is the only way architecture can create or connect with a specific sense of identity. This requires addressing the structural and local circumstances. This method handbook offers a playful way in which to systematically ascertain a complex framework and use it for your own design. The "9 x 9 method" takes all relevant factors and their alternate interaction into consideration: location, structure, shell, program, and materiality, all which, in a matrix with various intersections, produce exactly 9 "fields of action" for the design. The individual "fields" are not only illustrated visually with meaningful and eidetic pictures, but are also discussed in texts by leading specialists. For this book, the "9 x 9 method" was completely re-worked and redesigned